Analisis Indeks Pembangunan Manusia Di Indonesia Periode 2020-2023 - Anzani, Nur; Sri Widya Rahayu; Odi Gunawanta Sembiring; Muhammad Rizky Ashari Parinduri; Yesi Aulia Sari; Serina Regita Cahyani; Rakha Arya Putra; Gadis Arniyati Athar (CV. Ulil Albab Corp, 2025)
The purpose of this study is to ascertain the Human Development Index (HDI) and AHH in 35 districts and cities in Indonesia from 2020 to 2023. This study adopts a descriptive qualitative approach. In data collection, this study applies a documentation method, which involves citing or copying relevant documents as data sources for analysis. In this study, secondary and primary data will be applied, including the Human Development Index (HDI) with a data time range from 2020 to 2023. The methodology applied is qualitative analysis. The results of the analysis indicate that the Human Development Index (HDI) at the district/city level for the 2020-2023 period recorded an average of 73.17, while the national average figure in the same period reached 75.02. With the average Human Development Index (HDI) recorded and an increase of 8.36 points, the HDI achievement for districts/cities is classified in the